2018
DOI: 10.1061/(asce)nh.1527-6996.0000282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quantitative Precipitation Predictions by ECMWF, CMA, and UKMO for Flood Forecasting: Application to Two Basins in China

Abstract: Numerical weather predictions (NWPs) are very useful in hydrological modeling, including for river flow forecasting and flood warning in river basins. However, uncertainties in NWPs also significantly impact the accuracy of streamflow forecasting. Therefore, evaluating the accuracy of NWPs is crucial to achieve reliable streamflow forecasts. In this study, rainfall prediction skills of three NWP models [developed by the European Centre for Medium-Range Weather Forecasts (ECMWF); the U.K. Meteorological Office … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The ORACLES team decided on separate deployments in September 2016, August 2017, and October 2018, a decision that was aided by a relative lack of interannual variability in meteorology. This variability was predominantly linked to SST variations known as Benguela Niños that mainly occur in boreal spring, not fall, and are much less frequent than the better-known Pacific El Niños (Rouault, 2012). Interannual variability in fire emissions was expected to be low as well (van der Werf et al, 2010).…”
Section: Motivation For 3-year Field Deploymentmentioning
confidence: 99%
“…The ORACLES team decided on separate deployments in September 2016, August 2017, and October 2018, a decision that was aided by a relative lack of interannual variability in meteorology. This variability was predominantly linked to SST variations known as Benguela Niños that mainly occur in boreal spring, not fall, and are much less frequent than the better-known Pacific El Niños (Rouault, 2012). Interannual variability in fire emissions was expected to be low as well (van der Werf et al, 2010).…”
Section: Motivation For 3-year Field Deploymentmentioning
confidence: 99%
“…the radiation measurements of some instruments (e.g., 4STAR, SSFR). Verification studies prior to the ORACLES 365 deployments showed that the European Centre for Medium Range Weather Forecasts (ECMWF;Pappenberger et al, 2008;ECMWF Newsletter, 2012;Ye et al, 2014) and United Kingdom Meteorological Office (UKMO; Ran et al, 2018) global forecast models provided the best performance for cloud forecasts. ECMWF digital data were available at 0.125° longitude x latitude resolution, and included the primary meteorological variables (relative humidity and horizontal winds at 925, 850, 800, 700, 600, 500, 400, 300, 150, and 100 hPa levels; 1000-500 hPa layer thickness; 370 surface wind speed; mean sea level pressure; boundary layer height; precipitation; convective available potential energy) as well as 3-D ice and liquid water mass.…”
Section: Experiments Strategy: Forecasting and Flight Planningmentioning
confidence: 99%
“…These characteristics thus called for big and not conventional data handling. It would be later shown in the subsequent experiments that the rainfalls big data forecasted by ECMWF model yielded the most accurate results [61].…”
Section: Data Integrationmentioning
confidence: 93%
“…In terms of mathematical models, it was found that current frameworks made their flood forecast based on three models, i.e., meteorological, hydrological, and ML ones. The first two models were used with many algorithms, e.g., HEC-HMS [57], HEC-RAS [59], Mike11 [60], Mike21 [60], Mike-Flood [60], and ECMWF [61], etc., while those using ML model were implemented with various methods (as discussed in the section I. E). Thus far, these systems were only experimental and, to our knowledge, not yet publicly distributed.…”
Section: F Flood Forecasting Frameworkmentioning
confidence: 99%